Description of a new species of Terminalichus (Acari: Trombidiformes: Tenuipalpidae) from China - Xu, Yun; Fan, Qing-Hai; Huang, Jian (Zootaxa, 2014)
A new species Terminalichus sanya Xu & Fan sp. nov. (Acari: Tenuipalpidae) on Terminalia catappa L. (Combretaceae) from China is described and illustrated. The ontogenetic changes in ventral and leg chaetotaxy on the female, deutonymph, protonymph and larva are presented. The generic definition of Terminalichus is updated and a key to the world species is provided.